2022
DOI: 10.3390/medicina58121802
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Simultaneous Resection of Gastric Carcinoma and Synchronous Liver Metastasis—A Western Center Experience

Abstract: Background and objectives: Gastric cancer (GC) is often diagnosed in the metastatic stage. Palliative systemic therapy is still considered the gold standard, even for patients with resectable oligometastatic disease. The aim of the current study is to assess the potential benefit of up-front gastric and liver resection in patients with synchronous resectable liver-only metastases from GC (LMGC) in a Western population. Materials and Methods: All patients with GC and synchronous LMGC who underwent gastric resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In group B were hepatectomy is performed the rearrangement of the patient's position takes less time. We use the Pringle maneuver to control liver inflow [16][17][18][19][20][21]. Although, sometimes lower volume may is observed which causes circulatory disorders in organs, and therefore performing the Pringle should be used only when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In group B were hepatectomy is performed the rearrangement of the patient's position takes less time. We use the Pringle maneuver to control liver inflow [16][17][18][19][20][21]. Although, sometimes lower volume may is observed which causes circulatory disorders in organs, and therefore performing the Pringle should be used only when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GCLM generally experience unfavorable outcomes, often encounter early death, and encounter signi cant controversy regarding comprehensive treatment approaches. (11,12,13,14) In recent years, the early mortality of GCLM patients has attracted widespread attention among medical researchers. However, reports on cancer-speci c early mortality and associated factors in GCLM patients are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Minciuna et al [22] reported on retrospective study to assess the potential benefit of up-front liver and/or primary gastrectomy in patients with potentially resectable gastric cancer (GC) and synchronous OMD (less than 3 metastases) limited to the liver. Out of 28 patients fulfilling the inclusion criteria, 16 underwent simultaneous gastric and liver resection (simultaneous resection, while 12 underwent palliative gastric resection alone.…”
Section: Clinical Studies Of Omd In Og Cancermentioning
confidence: 99%